PENDIDIKAN KESEHATAN PADA ANAK SEKOLAH DENGAN METODE ROLE PLAY UNTUK MEMINIMALKAN DISTRES HOSPITALISASI - Eva Oktaviani; Susmini .; Jhon Feri (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
School age is a time when it is prone to various diseases, so it is not uncommon for children to be hospitalized. Being treated in a hospital (hospitalization) is an unpleasant and distressing experience of a child's crisis. Distress during hospitalization can affect health status. Efforts to reduce anxiety are very important when the child has not been treated as a preventive measure. The purpose of this community service activity is to increase children's knowledge about techniques to reduce hospitalization distress. The method used is health education with the role play method. The number of activity participants was 15 grade 4 elementary school students. Evaluation of the activity using pre and posttest scores. There was an increase in the mean score from the pre-test which was categorized quite good (53.4%) to be good at the posttest score (86.7%). Health education with the role play method can increase the knowledge of elementary school students to minimize negative experiences when the child is hospitalized. The introduction of the hospital environment from an early age can be applied as a pre-hospital effort to provide an overview of children's knowledge about hospital care procedures.